Chaperonin Abundance Enhances Bacterial Fitness - Kumar, C. M. Santosh; Chugh, Kritika; Dutta, Anirban; Mahamkali, Vishnuvardhan; Bose, Tungadri; Mande, Sharmila S.; Mande, Shekhar C.; Lund, Peter A. (Frontiers in Molecular Biosciences, 2021)
The ability of chaperonins to buffer mutations that affect protein folding pathways suggests that their abundance should be evolutionarily advantageous. Here, we investigate the effect of chaperonin overproduction on cellular fitness in Escherichia coli. We demonstrate that chaperonin abundance confers (a) an ability to tolerate higher temperatures, (b) improved cellular fitness and (c) enhanced folding of metabolic enzymes, which is expected to lead to enhanced energy harvesting potential.